The effect of activation of background knowledge reading strategy on students’ reading comprehension performance: a case study - Mansor, Noraien; Mohamed Zuldin, Nik Nurhidayah; Abd Rahim, Normaliza (Serials Publications, 2017)
This study examined the effect of background knowledge reading strategy among ESL learners as well as to identify the pre-reading strategies that are commonly used by the students. The sample comprised of 160 form one students from one of the semi-urban schools in Kuala Terengganu. The quasi–experimental design was used in the study. Students were divided into experimental and controlled groups. Modules were designed for the purpose of this research which contained six reading texts with ten comprehension questions for each text. For the experimental group, pre-reading activities were included in the module as the intervention. The English Language teachers conducted the module in their respective reading classes. Students were asked to answer the questions based on the module prepared for them. After the module session was done, ten students from the experimental group were selected for Think Aloud Protocol (TAP) session and interviews. The reading comprehension tasks were analysed to investigate the performance between the experimental and controlled groups. The result of the Think Aloud Protocol (TAP) sessions and interviews were analysed by the researchers to support the result of the reading comprehension marks. The study revealed that the reading strategy helped students from the experimental group in their reading comprehension performance. The findings of this study had revealed that there is significant improvement in the reading comprehension performance of the lower secondary students after being exposed to activation of background knowledge reading strategy.